Common Mycorrhizae Network: A Review of the Theories and Mechanisms Behind Underground Interactions - Figueiredo, Aline Fernandes; Boy, Jens; Guggenberger, Georg (Frontiers in Fungal Biology, 2021)
Most terrestrial plants establish symbiotic associations with mycorrhizal fungi for accessing essential plant nutrients. Mycorrhizal fungi have been frequently reported to interconnect plants via a common mycelial network (CMN), in which nutrients and signaling compounds can be exchanged between the connected plants. Several studies have been performed to demonstrate the potential effects of the CMN mediating resource transfer and its importance for plant fitness. Due to several contrasting results, different theories have been developed to predict benefits or disadvantages for host plants involved in the network and how it might affect plant communities. However, the importance of the mycelium connections for resources translocation compared to other indirect pathways, such as leakage of fungi hyphae and subsequent uptake by neighboring plant roots, is hard to distinguish and quantify. If resources can be translocated via mycelial connections in significant amounts that could affect plant fitness, it would represent an important tactic for plants co-existence and it could shape community composition and dynamics. Here, we report and critically discuss the most recent findings on studies aiming to evaluate and quantify resources translocation between plants sharing a CMN and predict the pattern that drives the movement of such resources into the CMN. We aim to point gaps and define open questions to guide upcoming studies in the area for a prospect better understanding of possible plant-to-plant interactions via CMN and its effect in shaping plants communities. We also propose new experiment set-ups and technologies that could be used to improve previous experiments. For example, the use of mutant lines plants with manipulation of genes involved in the symbiotic associations, coupled with labeling techniques to track resources translocation between connected plants, could provide a more accurate idea about resource allocation and plant physiological responses that are truly accountable to CMN.